2021
DOI: 10.3390/cancers13040721
|View full text |Cite
|
Sign up to set email alerts
|

Perineal Wound Closure Following Abdominoperineal Resection and Pelvic Exenteration for Cancer: A Systematic Review and Meta-Analysis

Abstract: Background. Abdominoperineal resection (APR) and pelvic exenteration (PE) for the treatment of cancer require extensive pelvic resection with a high rate of postoperative complications. The objective of this work was to systematically review and meta-analyze the effects of vertical rectus abdominis myocutaneous flap (VRAMf) and mesh closure on perineal morbidity following APR and PE (mainly for anal and rectal cancers). Methods. We searched PubMed, Cochrane, and EMBASE for eligible studies as of the year 2000.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…Findings for MCF reconstruction were similar, although rates of perineal wound morbidity and reoperation were high. These findings are consistent with those of a systematic review by Buscail et al [36]. They concluded that although patients who underwent MCF reconstruction following APR had reduced total and major wound complications (compared with primary closure), in patients who underwent MCF reconstruction post-PE, there were increased major and total perineal wound complications.…”
Section: Discussionsupporting
confidence: 89%
“…Findings for MCF reconstruction were similar, although rates of perineal wound morbidity and reoperation were high. These findings are consistent with those of a systematic review by Buscail et al [36]. They concluded that although patients who underwent MCF reconstruction following APR had reduced total and major wound complications (compared with primary closure), in patients who underwent MCF reconstruction post-PE, there were increased major and total perineal wound complications.…”
Section: Discussionsupporting
confidence: 89%
“…13 Contrary to this, recent systematic reviews, meta-analysis and a randomized control trial have found myocutaneous flaps to lower perineal wound morbidity. 4,12,29 Nonetheless, previous NSQIP studies have combined anal and rectal cancer into a single cohort potentially skewing the results. 13,15 Utilizing solely anal cancer is crucial as morbidity and wound complication rates are known to differ between rectal and anal cancer APR’s.…”
Section: Discussionmentioning
confidence: 99%
“…2 The nature of the resection from APR's often inherently results in substantial perineal defects that become a challenge to close in a tension free fashion, and complications of wound healing as a result of this occur frequently. 4 In addition, neoadjuvant radiotherapy increases the risk of impaired wound healing and contributes to the significant morbidity associated with APR. 5 Historically, wound complications were reported to occur at 40-45%, but in recent years, these rates can be as high as 60-70%.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple surgical options for closure of perineal defects have been described: primary closure, use of acellular dermal matrix, loco-regional flaps, and pedicled muscular flaps. Two studies demonstrated the superiority of muscular flaps compared to primary closure [ 1 , 17 ]. VRAM and gracilis are two popular muscle flaps used in perineal reconstruction, motivating their comparison in this meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Flaps have been shown to resist bacterial infection in vivo and favor wound healing by providing a steady blood supply that delivers oxygen, immunological cells, and antibiotics to the defect site [ 10 , 15 , 16 ]. A wide variety of techniques exist to reconstruct perineal defects following oncologic resection, but muscular pedicled flaps have gained interest among professionals due to their robust blood supply, the absence of microsurgical anastomosis, and their ability to offer tension-free closure [ 1 , 17 , 18 ]. Among them, VRAM and gracilis are two popular options [ 1 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%